Potencial Miogênico Evocado Vestibular Cervical (cVEMP) em crianças e adolescentes com aqueduto vestibular alargado : revisão sistemática. - Santos, Larissa Bomfim (2023)
The enlarged vestibular aqueduct syndrome is a disease characterized by an increase in the connection between the endolymphatic sac and the vestibule, with a variable clinical picture that usually starts in childhood with hearing loss that varies from moderate to severe and vestibular dysfunction. Among the possible tests used in the otoneurological evaluation of patients with an enlarged vestibular aqueduct there is the cervical vestibular evoked myogenic potential (cVEMP). Objective: To compile the parameters found in cVEMP in children and adolescents with an enlarged vestibular aqueduct and to identify possible changes when compared to values found in normal hearing patients of the same age group. Method: Systematic review registered on PROSPERO, developed from the search in virtual databases: Science Eletronic Library Online (SciELO), PubMED, Latin American and Caribbean Literature on Health Sciences (LILACS, via VHL), Scopus, Web of Science, Science Direct, Google Scholar, BASE and CORE from the keywords "vestibular evoked myogenic potential", "child", "adolescent", "large vestibular aqueduct" and their equivalents in Portuguese. After defining the eligibility criteria, the collection was selected, and those included were synthesized, read, and interpreted qualitatively. Results: 984 records were identified from the search in the consulted databases and five articles were selected. In a total of 133 patients who underwent cVEMP, we observed response in most cases, with no significant difference in latencies, but with increased amplitude and decreased thresholds. Conclusion: The cVEMP test is recommended in the evaluation of children and adolescents with enlarged vestibular aqueduct syndrome, and the characteristics of increased amplitude and decreased thresholds may be used as clinical parameters in the identification of this syndrome together with the patient's clinical history and imaging tests. However, it is still necessary to carry out more studies with the cVEMP test in children and adolescents with enlarged vestibular aqueduct for a better standardization of the values found and ease of early diagnosis.